Host Record, Description of Male and First Record of Proleurocerus litoralis Hayat and Kazmi (Hymenoptera: Chalcidoidea: Encyrtidae) from Doon Valley, Uttarakhand, India - Singh, Sudhir (Indian Forester, 2010)
Hayat and Kazmi (1996) described encyrtid species Proleurocerus litoralis from the sweep collected material from Kerala. In the present study Proleurocerus litoralis have been recorded from the Doon Valley in northern India. It was bred from egg masses of Eurybrachys tomentosa (Homoptera: Fulgoridae) which forms the first host record of the species. This species was earlier known by its females only; in the present study male of this species have also been described in details.